Security Aspects of Grid-based Digital Mammography - Slaymaker, M. A.; Politou, E.; Power, D. J.; Lloyd, S.; Simpson, A. C. (Methods of Information in Medicine, 2005)
Objectives: The principal aim of the eDiaMoND project is to develop a prototype Grid infrastructure to support the needs of the breast care community. The prototype system is but one major deliverable of the project; the other is a blueprint document that describes how a system such as eDiaMoND might be deployed throughout the United Kingdom to support the NHS Breast Screening Programme. A key consideration of both the prototype and the blueprint is security. In this paper we address some of the generic security issues faced by projects such as eDiaMoND. We also indicate how these problems are being overcome within our project.Methods: In order to fully understand the security issues faced by the project a review of current initiatives within the NHS was performed. The work of the NHS Information Authority was found to be particularly significant. Also reviewed was BS7799, the British Standard for the deployment of security systems and processes. Finally, modelling of the proposed prototype was performed using methods proposed by the e-Science Security Task Force, in particular the method proposed by Flechais and Sasse.Results and Conclusions: It is felt that the issues of security surrounding the eDiaMoND project are sufficiently generic that the eHealth community can consider and criticise the work described. It is hoped that this will enable the eHealth community to move forwards with a common agenda.
Keywords: Digital mammography; computer security; grid computing; e-science